Identifikasi Lokasi Potensial Mikrohidro Menggunakan Metode AHP dan SIG di DAS Sembakung Kalimantan Utara - Nurrohman, Andy Wibawa; Adyatma, Rafi; Awaliah, Rohmatul Arsy; Fadilah, Hasna Rizqi (LaGeografia, 2025)
Microhydro Power Plant (MHP) is a promising renewable energy solution for remote rural areas that have not been reached by electricity, especially in areas with abundant water resources. This study aims to identify potential locations for MHP development in the Sembakung Watershed, North Kalimantan, by integrating the Analytical Hierarchy Process (AHP) and Geographic Information System (GIS) methods. Seven spatial parameters were used in the analysis, namely elevation, slope, distance from the river, land cover, number of electricity customers, and level of ground motion vulnerability. Each parameter was weighted using AHP based on its level of influence on the feasibility of MHP development, and processed in GIS to produce a location suitability map. The results of the analysis show that the Lumbis Ogong sub-district area has a high level of suitability for MHP development, supported by ideal geographical characteristics and urgent electrical energy needs. This study shows that the AHP-SIG approach is effective in supporting spatial decision-making and can be a local potential-based renewable energy planning strategy. The findings also provide an opportunity to sustainably accelerate rural electrification in Indonesia's border regions, which are still lagging in terms of energy infrastructure.